Effects of a short message service (SMS) by cellular phone to improve compliance with fasting guidelines in patients undergoing elective surgery: a retrospective observational study - Faizan Zia; Luka Cosic; Angela Wong; Adam Levin; Patrick Lu; Craig Mitchell; Michael Shaw; Fred Rosewarne; Laurence Weinberg (BMC, 2021)
Abstract Background Contemporary perioperative fasting guidelines aim to alleviate patient discomfort before surgery and enhance postoperative recovery whilst seeking to reduce the risk of pulmonary aspiration during anesthesia. The impact of a short message service (SMS) reminder on fasting guideline compliance is unknown. Therefore, we performed a retrospective observational study and quality improvement project aiming to quantify the extent of excessive and prolonged fasting, and then assessed the impact of a SMS reminder in reducing fasting times. Methods After ethics committee approval we performed a retrospective observational study investigating preoperative fasting times of adult patients undergoing elective surgery. First, we assessed whether the fasting guideline times were adhered to (Standard Care group). All patients received internationally recommended fasting guidelines in the form of a written hospital policy document. We then implemented an additional prompt via a mobile phone SMS 1 day prior to surgery containing a reminder of fasting guideline times (SMS group). The primary aims were to compare fasting times between the Standard Care group and the SMS group. Results The fasting times of 160 patients in the Standard Care group and 110 patients in the SMS group were evaluated. Adherence to the fasting guidelines for solids occurred in 14 patients (8.8%) in the Standard Care group vs. Twenty-two patients (13.6%) in the SMS group (p=0.01). Adherence to the fasting guidelines for fluids occurred in 4 patients (2.5%) in the Standard Care group vs. Ten patients (6.3%) in the SMS group (p=0.023). Patients in the Standard Care group had a longer median (inter-quartile range (IQR)) fasting time for fluids compared the SMS group [6.5 h (IQR 4.5:11) vs 3.5 h (IQR 3:8.5), p< 0.0001]. Median fasting times for solids were 11 h (IQR 7:14) in the Standard Care group and 11.5 h (IQR 7:13.5) in the SMS group (p=0.756). Conclusion Adherence to internationally recommended fasting guidelines for patients undergoing elective surgery is poor. The introduction of a fasting guideline reminder via a mobile phone SMS in addition to a written hospital policy improved adherence to fasting advice and reduced the fasting times for fluids but not for solids. The use of an SMS reminder of fasting guidelines is a simple, feasible, low-cost, and effective tool in minimising excessive fasting for fluids among elective surgical patients. Trial registration ACTRN12619001232123 (Australia New Zealand Clinical Trials Registry). Registered 6th September 2019 (retrospectively registered).